Shattering silos : reimagining knowledge, politics, and social critique - Zuidervaart, Lambert (McGill-Queen's University Press, 2022)
"Questions first raised by Hannah Arendt in the 1960s take on new urgency in the post-truth era, as political leaders blithely reject facts in the public domain: Is truth politically impotent? Are politics inherently false? Is the search for truth still relevant? Shattering Silos, a companion volume to Religion, Truth, and Social Transformation and Art, Education, and Cultural Renewal, provides a path-breaking response. As in his two previous books, Lambert Zuidervaart challenges the boundaries philosophers set up between epistemology, ethics, and political philosophy. Knowledge, he argues, takes different forms in various social domains, and all are subject to political struggle. A critique of contemporary society must draw on many social domains of knowledge, including the arts and religion, and should recast politics as a striving for truth in the broadest sense. Proposing a new conception of truth--one that emphasizes the unity of knowledge and truth, as well as their diversity among different social domains--Zuidervaart asks what such holism and pluralism suggest about how we understand politics and society. This book proposes a new understanding of large-scale social change, challenging how most people think about knowledge and truth. Interweaving epistemology, social criticism, and political thought, Shattering Silos aims to help redirect an allegedly post-truth society."--